BIMBINGAN BELAJAR (BIMBEL) MATEMATIKA DI DESA SINAR GADING - Ananda Tri Astuti Riatma; Muhammad Jainuri; Ade Susanti (AbdiMasya | Hira Institute, 2023)
Community Empowerment Learning Activities (PPM) in 2023 aims to create an innovative and dignified village. In this activity the author chose the Mathematics Tutoring Activity Program (BIMBEL) in Sinar Gading Village. This tutoring aims to overcome learning problems at home, to increase interest, talent and motivation of elementary and MI students in Sinar Gading Village. The target audience for this tutoring is students at SD N 242 Sinar Gading and MI Darussalam. This tutoring will be held at Post 7 PPM Sinar Gading Village in 2023 for 3 weeks. The learning model used is a direct or face-to-face learning model, using lecture and discussion methods. The results obtained during this tutoring activity are that there are still many students who have a high interest in learning